Air Warming and Drainage Influences Soil Microarthropod Communities - Zhang, Hui; Sun, Xin; Liu, Dong; Wu, Haitao; Chen, Huai (Frontiers in Ecology and Evolution, 2021)
The degradation of wetlands due to climate change is of critical concern to human beings worldwide. Little is known about the potential synergistic effects of simultaneous water level reduction and warming on the underground wetland ecosystems. We conducted a 5-month field experiment in the Sanjiang Plain, utilizing open-top chambers and water level automatic control systems to investigate such synergistic effects. Soil springtails (Collembola) and mites (Acari) in the top (0–20 cm) soil layers were sampled to calculate their density, diversity, and to screen for indicator species. Warming significantly influenced soil springtail communities, slightly increasing the total density and total abundance under the natural water level while reducing them under a constant water level. In addition, Anurida maritima and Vertagopus laricis, two indicators for the natural water level, had the highest densities in the natural water level treatment and under the combined treatment of warming and natural water level, respectively. Cheiroseius sinicus and Malaconothrus tardus had the highest densities in warming under the 0 cm water level, significantly higher than the other three treatments. This study also revealed the importance of maintaining fluctuating water levels for microarthropod communities influenced by global warming, providing a theoretical basis for water level control in wetland restoration.